Effectiveness and Significance of Nepal Tourism Years - Bhatt, Roshan (Brixton Scholarly Review, 2025)
This study explores the effectiveness of Nepal’s tourism campaigns, including Visit Nepal 1998, Nepal Tourism Year 2011, and the postponed Visit Nepal 2020, aiming to boost tourist arrivals, economic growth, and regional development. Employing a cross-sectional study approach and analyzing secondary data from the Nepal Tourism Board and other credible sources, the study evaluates key metrics such as tourist arrivals, foreign exchange earnings, and infrastructural improvements. Findings indicate that while campaigns have spurred growth in central regions, rural areas remain underserved. The study highlights the need for inclusive tourism policies that address regional disparities, thereby supporting a more equitable distribution of tourism benefits across Nepal. Limitations include a reliance on existing data, which may affect comprehensiveness. These insights hold value for policymakers and tourism authorities as they seek to create sustainable and balanced tourism development strategies.